Stability-indicating LC method for the determination of cephalothin in lyophilized powder for injection - Rugani, Karen de Souza [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Royal Soc Chemistry, 2014)
A stability-indicating gradient reversed phase liquid chromatography (RP-LC) method has been developed for the quantitative determination of cephalothin (CET), an antimicrobial compound, in the presence of its impurities and degradation products generated from forced degradation studies. The developed method is also applicable for related substance determination in bulk drugs. The chromatographic separation was achieved on an Agilent Eclipse XDB-Phenyl, 250 mm x 4.6 mm, 5 mu m column with a mobile phase containing a gradient mixture of solutions A (aqueous ammonium phosphate buffer, pH 4.5) and B (acetonitrile). The flow rate was 1.0 mL min(-1) and the detection wavelength was 238 nm. The drug substance was subjected to stress conditions of hydrolysis, oxidation, photolysis, humidity and thermal degradation. Considerable degradation was found to occur in basic, acidic and oxidative stress conditions. In the developed high performance liquid chromatography (HPLC) method, the resolution between CET and its potential degradation products was found to be greater than 2.4. Further, the peak purity of CET in all conditions was more than 99% and proved the stability-indicating power of this method. The less active metabolite of cephalothin, deacetylcephalothin (impurity B), was identified and showed significant formation especially in basic conditions. This method is capable of detecting the degradation products of CET at a level of 0.05% with respect to the test concentration of 500 mu g mL(-1) for a 10 mu L injection volume. The developed HPLC method was validated with respect to linearity, accuracy, precision, specificity, limit of quantitation, limit of detection and robustness. To our knowledge, a rapid stability-indicating LC method for CET has not been published elsewhere and this method can be applicable to the evaluation of the quality of product samples as well as in stability studies of cephalothin.